The Influence of Price, Promotion, Product Quality and Location on Gold Jewelry Purchasing Decisions at the Nirwana Gold Shop, Martapura City, Banjar Regency, South Kalimantan - Audah, Zidan; Soegiri, Hary; Anastasia, Maria; Kadir, Abdul (Universitas Hang Tuah, 2026)
This study aims to analyze the effects of price, promotion, product quality, and location on consumers’ purchasing decisions of gold jewelry at Nirwana Gold Shop in Martapura City, Banjar Regency, South Kalimantan. The research employed a quantitative approach using a survey method. Data were collected from 100 respondents who were customers of Nirwana Gold Shop, selected through purposive sampling. A structured questionnaire was used as the research instrument, and the data were analyzed using multiple linear regression analysis. The results indicate that price, promotion, product quality, and location simultaneously have a significant effect on purchasing decisions. Partially, all independent variables also show significant effects, with product quality emerging as the most dominant factor influencing purchasing decisions. These findings suggest that consumers’ decisions to purchase gold jewelry are not solely determined by price and promotional activities, but are also strongly influenced by product quality assurance and the strategic location of the store. Therefore, gold jewelry retailers are encouraged to implement integrated marketing strategies by maintaining high product quality, offering competitive pricing, conducting effective promotional activities, and selecting strategic business locations to enhance competitiveness and consumer loyalty.